Urban open space management in the Nordic countries. Identification of current challenges based on managers' perceptions. (August 2021) - Randrup, T.B.; Svännel, J.; Sunding, A.; Jansson, M.; Sang, Å.O.
Abstract: This paper reports on how Nordic practise relates to, and perceives contemporary challenges to urban open space management. The study used a case study approach, via interviews. The studied Nordic cities experience the effects of densification in inner city areas. This is often resulting in higher pressure on existing urban open spaces, but also generating new spaces which tend to be small and fragmented, not meeting the many wishes and demands asked for by the diverse user groups. While budgets are sufficiently allocated in new development projects, it is a challenge to withstand the maintenance budgets, forcing managers to prioritise. Due to primary political interest in inner city areas, there is a risk of managers not prioritising the more peripheral areas, from where resources are often transferred to the newly developed areas. This creates a new type of urban nature, primarily in the urban peripheral areas, with increased amounts of biodiversity and higher amounts of multi-functionality, compared to the smaller and more intensively programmed inner-city areas. Urban open space managers are relying on the existing municipal planning tools, and to varying degrees act strategically in terms of developing own sector oriented plans and strategies. Highlights: Urban open space managers' perceptions revealed four main contemporary challenges. Urban densification is perceived as a main challenge, leading to More, but smaller, green spaces in inner city areas Urban open space quality is related to relevance for users 4. There is a wish for more policy-oriented facts and documentation of urban open space values for users.